Perspectives in particle physics '94 proceedings of the 7th Adriatic Meeting on Particle Physics, Brijuni, Croatia, 13-20 September 1994 (World Scientific Publishing Co. Pte Ltd., 1995)
"The Adriatic conferences used to be topical meetings, organized in three-year intervals. However, the postponement of the Meeting has to some extent broadened the subjects which have been covered this year. The Meeting has covered several interconnected and currently interesting topics in particle physics - ranging from electroweak phenomenology testing the standard theory, including perturbative and non-perturbative QCD, chiral perturbation theory, bound-state calculations, finite-temperature theory, neutrino physics, heavy-quark effective theories, Higgs and top physics, rare decays and CP violation in K- and B-physics - up to nonaccelerator physics and field-theoretical methods at interfaces to solid state physics and cosmology. We have arranged the contents of this volume in five sections as follows: QCDoing; Hadronic Physics; Electroweak Physics; Te V Energy Physics / Beyond the Standard Model; Astroparticle / Cosmology. This brings the Proceedings to the form of a modern book on particle physics, in which both professionals and students could find enjoyable chapters."--Foreword